ANALISIS ARUS HUBUNG SINGKAT DI PT PLN NUSANTARA POWER UP GRESIK PADA MOTOR BOILER FEED PUMP - Harista Rahman, Alvin; Budiyanto, Maun (Jurnal Teknologi dan Vokasi, 2024)
Reliability is the main characteristic that must be maintained in power generation units in line with the increase in electricity consumption in Indonesia. If this reliability cannot be maintained, it will damage the generating equipment and disrupt the distribution of electricity supply to the loads. Failure in the reliability of the power generation unit can be caused by short circuit fault current conditions. In this study, an analysis was carried out regarding the condition of the short circuit current in the electricity network at the load of the 4A boiler feed pump (BFP) motor PT PLN Nusantara Power UP Gresik. Analysis was carried out to determine the maximum and minimum short circuit current conditions using ETAP 12.6 software. There are two bus bars that are used as simulation objects when experiencing disturbances, namely the 15 kV busbar and the 4.16 kV M/C switchgear busbar. The simulation results obtained are the maximum and minimum short circuit values. The maximum value is obtained from transient conditions in the form of a three-phase fault and one phase to ground. While the minimum value is obtained from the steady state condition in the form of an inter-phase fault current.